'China's leading historical and cultural city': Branding Dali City through public–private partnerships in Bai architecture revitalization. (December 2015) - Zhao, Yawei
Highlights: PPP in heritage management functions as an effective approach to city branding. City branding, though welcomed by local people, has negative externalities. The general public in China requests transparency of PPP. Abstract: Competing with other Chinese cities for investment and tourism, various governmental bodies with jurisdiction in Dali City have begun to make use of local historical and cultural assets in order to brand the city. This paper aims to reveal how partnerships between the public and private sectors in heritage management have functioned as an approach to city branding, and how local people perceive and are influenced by these partnerships. Applying perspectives from the scholarly literature on city branding and public–private partnerships, this paper examines two cases in Dali City – Zhang's Garden and the Linden Center – to detail how local government and elite entrepreneurs have partnernered in support of Bai architecture revitalization with tourism in mind. This paper also considers opinions from the local general public regarding these partnerships, and investigates the complex relationships among local government, elite entrepreneurs, and the public.